Leadership Style and Job Satisfaction among Generation MZ Employees in Bekasi, Indonesia: The Mediating Role of Work Engagement - Rio Nardo; Indri Guslina (Global Research Collaboration, 2026)
This study examines the relationship between leadership style and job satisfaction among Generation MZ employees in Bekasi, Indonesia, with work engagement as a mediating variable. Using a quantitative cross-sectional approach, data were collected from 341 employees and analyzed using PLS-SEM. The findings reveal that eadership style was positively associated with both work engagement and job satisfaction. In addition, work engagement significantly influences job satisfaction and partially mediates the relationship between leadership style and job satisfaction. These findings suggest that supportive leadership practices are associated with higher employee satisfaction both directly and indirectly through enhanced work engagement among Generation MZ employees in Bekasi, Indonesia. This study contributes to the literature on generational workforce management and leadership behavior in emerging economies. However, the findings should be interpreted cautiously due to discriminant validity limitations between several constructs.